Digital preservation and libraries. (VINE, 2004)
The concept of representation format permeates all technical aspects of digital repository architecture and is, therefore, the foundation of many, if not all, digital preservation activities. Digital formats need to be understood both as general classes of encodings and in the specific instances of digital objects. The Digital Library Foundation (DLF) has sponsored an initial investigation into the creation of a global digital format registry (GDRF) to maintain format representation information. Using such information, ancillary tools and services can be created for additional repository and p.